2008
DOI: 10.1074/jbc.m706623200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cyclin A2 as the Downstream Effector of the Nuclear Phosphatidylinositol 4,5-Bisphosphate Signaling Network

Abstract: In addition to the well characterized phosphoinositide second messengers derived from the plasma membrane, increasing evidence supports the existence of a nuclear phosphoinositide signaling network. The aim of this investigation was to dissect the role played by nuclear phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) in cell cycle progression and to determine the cell cycle regulatory component(s) that are involved. A number of cytosolic/nuclear PtdIns(4,5)P 2 -deficient Swiss 3T3 cell lines were estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The previous sections highlight just a few examples of what we are beginning to learn about the diverse roles of phosphoinositides during development. The list of developmental processes that may depend upon regulated phosphatidylinositol metabolism can be expanded to include neurite extension and neuronal development, angiogenesis (Im and Kazlauskas, 2006), cytokinesis (Echard, 2008;Field et al, 2005;Wong et al, 2005), cell cycle regulation (Ho et al, 2008), and flagellar biogenesis (Wei et al, 2008) to name a few. Given their integral roles during development, it is not surprising that the misregulation of PIPs and PIP binding proteins has been implicated in a growing number of diseases and developmental disorders.…”
Section: Phosphoinositides In Diseasementioning
confidence: 99%
“…The previous sections highlight just a few examples of what we are beginning to learn about the diverse roles of phosphoinositides during development. The list of developmental processes that may depend upon regulated phosphatidylinositol metabolism can be expanded to include neurite extension and neuronal development, angiogenesis (Im and Kazlauskas, 2006), cytokinesis (Echard, 2008;Field et al, 2005;Wong et al, 2005), cell cycle regulation (Ho et al, 2008), and flagellar biogenesis (Wei et al, 2008) to name a few. Given their integral roles during development, it is not surprising that the misregulation of PIPs and PIP binding proteins has been implicated in a growing number of diseases and developmental disorders.…”
Section: Phosphoinositides In Diseasementioning
confidence: 99%
“…PtdIns(4,5) P 2 was also shown to bind to BASP1 (brain acid soluble protein 1) and this interaction promotes a co-repressive function by recruiting histone deacetylases [ 43 ]. Other data correlate changes in the levels of nuclear PPIns to cell cycle progression [ 12 , 44 , 45 ] or apoptosis via an interaction between nucleophosmin (NPM) and PtdIns(3,4,5) P 3 [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Swiss 3T3, it has been demonstrated that nuclear PtdIns(4,5)P 2 down-regulation caused a delay in phorbol ester-induced S phase entry and that this was at least in part channeled through cyclin A2 at the transcriptional level, identifying cyclin A2 as a downstream effector of the nuclear PtdIns(4,5)P 2 signaling network (Ho et al, 2008).…”
mentioning
confidence: 99%